The Relationship between Students’ Personality Traits and Their Achievement in Mathematics in Ogun State Nigeria - Taiwo, Abiodun Oluwadayo; Asanre, Akorede Ayoola; Arigbabu, Abimbola Ismail (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2026)
This study examines the relationship between students’ personality traits and their achievement in mathematics in Ogun State, Nigeria. A descriptive survey design was employed in the study. Three research questions guided the study. The study's population consisted of all students at Senior Secondary School Two (SSS2) in Ogun Central Senatorial District, Ogun State, Nigeria. Using a random sample method, ten (10) secondary schools in Ogun Central Senatorial District of the State were selected. From each school, forty-two (42) responders were chosen. This method was selected in accordance with particular standards, including the schools' size, type, location, and demographic makeup. The study's sample consisted of seven hundred and twenty (420) respondents from the Senior Secondary School II (SSSII) class. The instruments used for data collection are: NEO Personality Inventory (r= 0.79) using Cronbach's alpha technique and Mathematics Achievement Test (MAT) with reliability, r = 0.86 using Kuder Richardson formula 20 (K-R20). Multiple Regression Analysis (MRA) and Pearson Product-Moment Correlation (PPMC) were used as inferential statistics to analyze the data at the 0.05 level of significance. The results of the findings showed that conscientiousness, extroversion, and agreeableness have positive and significant influence on students’ academic performance in a public senior secondary school in Ogun State.